Ecological Specialization Within a Carnivorous Fish Family Is Supported by a Herbivorous Microbiome Shaped by a Combination of Gut Traits and Specific Diet - Escalas, Arthur; Auguet, Jean-Christophe; Avouac, Amandine; Seguin, Raphaël; Gradel, Antoine; Borrossi, Lucie; Villéger, Sébastien (Frontiers in Marine Science, 2021)
Animals have been developing key associations with micro-organisms through evolutionary processes and ecological diversification. Hence, in some host clades, phylogenetic distance between hosts is correlated to dissimilarity in microbiomes, a pattern called phylosymbiosis. Teleost fishes, despite being the most diverse and ancient group of vertebrates, have received little attention from the microbiome perspective and our understanding of its determinants is currently limited. In this study, we assessed the gut microbiome of 12 co-occurring species of teleost representing a large breadth of ecological diversity and originating from a single family (i.e. the Sparidae). We tested how host evolutionary history, diet composition and morphological traits are related to fish gut microbiome. Despite fish species having different microbiomes, there is no phylosymbiosis signal in this fish family, but gut length and diet had a strong influence on the microbiome. We revealed that the only species with a specialized herbivorous diet, Sarpa salpa had a 3.3 times longer gut than carnivorous species and such a long gut favor the presence of anaerobic bacteria typical of herbivorous gut microbiomes. Hence, dietary uniqueness is paired with both unique gut anatomy and unique microbiome.